2017
DOI: 10.1002/celc.201600760
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia on Reduced Graphene Oxide Sheets: Synergistic Catalyst with High Selectivity for H2O2 Electrogeneration

Abstract: In situ electrogeneration of hydrogen peroxide through the oxygen reduction reaction (ORR) represents a potentially greener route for wastewater treatment. However, the development of adequate catalysts following a two‐electron pathway with high selectivity and low overpotential is still of great importance. To address this issue, nanoparticles of zirconium oxide supported on reduced graphene oxide (rGO) sheets were prepared through a hydrothermal reaction, and the composite catalysts were tested for the ORR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The X‐ray diffraction (XRD) analysis of FeNC1 reveals that the catalyst contains small amounts of crystalline Fe and Fe 3 C phases (Figure 2b). The reflections corresponding to ZrO 2 residue are also evident; this originates from ball‐milling procedure and has shown to be rather inactive for ORR [47] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The X‐ray diffraction (XRD) analysis of FeNC1 reveals that the catalyst contains small amounts of crystalline Fe and Fe 3 C phases (Figure 2b). The reflections corresponding to ZrO 2 residue are also evident; this originates from ball‐milling procedure and has shown to be rather inactive for ORR [47] …”
Section: Resultsmentioning
confidence: 99%
“…The reflections corresponding to ZrO 2 residue are also evident; this originates from ball-milling procedure and has shown to be rather inactive for ORR. [47] The investigation of the graphitic and disordered carbon phases in FeNC1 catalyst was carried out by Micro-Raman spectroscopy. As expected for a disordered carbon material, the Raman spectrum shows two first-order bands, D 1 band corresponding to disordered carbon at 1350 cm À 1 and G band related to graphitic carbon at about 1580 cm À 1 (Figure 2c).…”
Section: Physicochemical Characterisationmentioning
confidence: 99%
“…Oxygen reduction reaction (ORR) is one of the most important reactions in renewable energy conversion of defects such as oxygen vacancies. [12,[19][20][21][22] As illustrated in Table S1, Supporting Information, [16,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] the activity of this class of materials is still low, that is, they require high overpotential even to achieve a modest current density, and do not reach the limiting current value expected for the reduction of oxygen to water by the four-electron pathway:…”
Section: Introductionmentioning
confidence: 99%
“…Oxides from metals belonging to groups 4 and 5 (Ti, V, Zr, Nb, Hf, Ta) have attracted interest in these fields, mainly due to their low cost compared to PGM catalysts, environmental compatibility, and excellent stability in acid medium. [ 12,16–19 ] It has been demonstrated that these oxides can have some activity toward ORR, if their stoichiometry is conveniently tailored to generate a high concentration of defects such as oxygen vacancies. [ 12,19–22 ] As illustrated in Table S1, Supporting Information, [ 16,18,21–35 ] the activity of this class of materials is still low, that is, they require high overpotential even to achieve a modest current density, and do not reach the limiting current value expected for the reduction of oxygen to water by the four‐electron pathway: 2O2+ 4H++4e2H2O E0=1.23 V versus RHE …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation